The Regulatory Role of α-Ketoglutarate Metabolism in Macrophages - Shaojuan Liu; Jie Yang; Zhenfang Wu (Mediators of Inflammation)
Macrophages are multifunctional immune cells whose functions depend on polarizable phenotypes and the microenvironment. Macrophages have two phenotypes, including the M1 proinflammatory phenotype and the M2 anti-inflammatory phenotype, which play important roles in many inflammatory responses and diseases. α-Ketoglutarate is a key metabolite of the TCA cycle and can regulate the phenotype of macrophage polarization to exert anti-inflammatory effects in many inflammation-related diseases. In this review, we primarily elucidate the metabolism, regulatory mechanism, and perspectives of α-ketoglutarate on macrophages. The regulation of macrophage polarization by α-ketoglutarate may provide a promising target for the prevention and therapy of inflammatory diseases and is beneficial to animal health.